Synthesis, Characterization, Antimicrobial And Antitumour Studies Of A Series Of Co(Ii) And Cu(Ii) Complexes Derived From Namidino-N1-Naphthylthiourea - G. KRISHNAN,; S. SUPRABHA, (International Journal of Pharma and Bio Sciences, 2012)
A series of Co(II) and Cu(II) complexes with N-amidino-N1- naphthylthiourea (L) have been synthesized and the nature of bonding and structure of complexes have been deduced from elemental analysis, IR, 1H NMR, electronic spectra, magnetic susceptibility and conductivity measurements. The physico chemical studies and spectral data reveals that the ligand acts as neutral bidentate and coordinates through S and N. An octahedral geometry has been suggested for all the complexes and are formulated as [ML2X2] where M = Co(II), Cu(II), X = Cl-, 3 NO− , NCS− . The complexes [CoL2Cl2] and [CuL2Cl2] have been subjected to thermal decomposition study. The in-vitro antimicrobial and antitumour properties of the ligand in comparison to their metal complexes have been evaluated and it is observed that the complexes show more potent activity than the ligand.